Implicit Motor Imagery for Chronic Pelvic Pain: A Cross-Sectional Case–Control Study. - Díaz-Mohedo, Esther; González-Roldán, Gloria; Muñoz-Gámez, Inmaculada; Padilla-Romero, Virginia; Castro-Martín, Eduardo; Cabrera-Martos, Irene; Sánchez-García, Clara (MDPI, 2023)
Implicit motor imagery (IMI), with an image laterality discrimination (LD) task, has been proposed as a useful therapeutic tool to restore body schema in patients with chronic pelvic pain (CPP). The aim of this study was to analyse the existence of differences between patients with CPP and healthy individuals in order to justify the use of IMI. An observational, cross-sectional study with non-probabilistic sampling was designed as a one-to-one matched case–control study. Through a web link designed for this purpose, a total of 40 abdominoperineal images were shown to 130 participants during the laterality task. Outcome measures were pain intensity (visual analogue scale, VAS), accuracy, response time (RT), and CPPQ-Mohedo score (Chronic Pelvic Pain Questionnaire—Mohedo). This was an observational, cross-sectional study with a total of 64 CPP patients and 66 healthy individuals. The comparative analysis between groups revealed significant differences in accuracy, CPPQ-Mohedo and VAS (p < 0.001), but not in RT; in patients with CPP, accuracy was correlated with a lower CPPQ-Mohedo score and RT and, the greater the pain intensity, the higher the CPPQ-Mohedo score and RT, and the lower the accuracy. In the LD task, the patients with CPP made more mistakes than the healthy individuals. IMI could be a useful and complementary tool in the therapeutic approach for patients with CPP.
Keywords: Ortopedia; Dolor pélvico; Chronic pain; Graded motor imagery; Pelvic pain; Body schema; Laterality discrimination; Brain changes